The impact of creative accounting practices on the volume of trading in stocks An analytical study of a sample of joint stock companies listed on the Iraq Stock Exchange - Ali Abbas Karim; Alaa Mahdi Hadi (The Scientific Journal of Cihan University– Sulaimaniya, 2017)
The research aims to shed light on the creative accounting practices in the financial reports and their impact on the volume of trading in the Iraqi market for securities. Starting from the problem of increasing the departments of companies to manage profits for the purpose of raising the value of its shares at times and to reduce their profits in order to reduce the taxes for the State. The research adopted the following main hypothesis: "Creative accounting practices affect the volume of trading in the Iraqi market for securities" The study examined the reports of a number of companies in the market, which received the highest volume during the research period and the application of the Miller model to reveal the practices of profit management, which is one of the methods of creative accounting in addition to the method of income preparation .The researcher reached a set of conclusions :the most important is that all companies practice the creative accounting in their financial statements issued, which affect the volume of trading in their names in the Iraqi market for securities .The researcher has reached a set of recommendations, most notably is the use of the Miller model by the auditors for the purpose of detection and measurement of creative accounting practices in the companies which they audit.